2012
DOI: 10.1016/j.jmatprotec.2012.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and mechanical characteristics of laser welding of Ti6Al4V and lead metal

Abstract: a b s t r a c tTitanium alloy Ti6Al4V and lead metal were welded using a continuous wave Nd:YAG laser. The influences of laser power, scanning velocity, and laser beam offset on weld morphology were investigated. Microstructure, chemical composition and mechanical properties of the joints were evaluated. Experimental results showed that fusion weld formed at the upper part of the weld and brazing weld with solder of Pb formed at the lower part of the weld under appropriate process condition. Interfaces were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…For friction welding, the low efficiency and welding defects are concerning. Alternatively, highpower-density laser has attracted enormous research interest and found its wide application in a broad branch of manufacturing areas including selective laser sintering and three-dimensional printing [1][2][3][4][5][6], surface nanostructuring [7][8][9][10][11][12], multimaterial joining and integration [13][14][15][16][17], material removal [18,19], and mechanical/optical property enhancements [20][21][22][23]. Characteristics, such as contact-free processing, good flexibility and tunablity, high efficiency, and throughput, make laser a feasible route for welding of 42CrMo [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…For friction welding, the low efficiency and welding defects are concerning. Alternatively, highpower-density laser has attracted enormous research interest and found its wide application in a broad branch of manufacturing areas including selective laser sintering and three-dimensional printing [1][2][3][4][5][6], surface nanostructuring [7][8][9][10][11][12], multimaterial joining and integration [13][14][15][16][17], material removal [18,19], and mechanical/optical property enhancements [20][21][22][23]. Characteristics, such as contact-free processing, good flexibility and tunablity, high efficiency, and throughput, make laser a feasible route for welding of 42CrMo [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Recently many new metal combinations were successfully joined by laser: Zhao et al (2013) report titanium/lead joining, Tomashchuk et al (2011) carried out titanium to steel welding via copper interlayer, Mathieu et al (2006) and Sierra et al (2007) carried out aluminum to steel welding.…”
Section: Introductionmentioning
confidence: 99%
“…High power density lasers have attracted intense research interest in various areas of advanced manufacturing [11][12][13][14][15][16][17][18][19][20][21][22] due to their high efficient, precise, and flexible material-processing features. The transport phenomena during laser-matter interaction is the key for their implementations.…”
Section: Introductionmentioning
confidence: 99%